CSI 2264: SIMULTANEOUS OPTICAL AND INFRARED LIGHT CURVES OF YOUNG DISK-BEARING STARS IN NGC 2264 WITH CoRoT and SPITZER —EVIDENCE FOR MULTIPLE ORIGINS OF VARIABILITY - Cody, Ann Marie; Stauffer, John; Baglin, Annie; Micela, Giuseppina; Rebull, Luisa M.; Flaccomio, Ettore; Morales-Calderón, María; Aigrain, Suzanne; Bouvier, Jèrôme; Hillenbrand, Lynne A.; Gutermuth, Robert; Song, Inseok; et al. (The Astronomical journal, 2014)
We present the Coordinated Synoptic Investigation of NGC 2264, a continuous 30 day multi-wavelength photometric monitoring campaign on more than 1000 young cluster members using 16 telescopes. The unprecedented combination of multi-wavelength, high-precision, high-cadence, and long-duration data opens a new window into the time domain behavior of young stellar objects. Here we provide an overview of the observations, focusing on results from Spitzer and CoRoT. The highlight of this work is detailed analysis of 162 classical T Tauri stars for which we can probe optical and mid-infrared flux variations to 1% amplitudes and sub-hour timescales. We present a morphological variability census and then use metrics of periodicity, stochasticity, and symmetry to statistically separate the light curves into seven distinct classes, which we suggest represent different physical processes and geometric effects. We provide distributions of the characteristic timescales and amplitudes and assess the fractional representation within each class. The largest category (>20%) are optical "dippers" with discrete fading events lasting ~1-5 days. The degree of correlation between the optical and infrared light curves is positive but weak; notably, the independently assigned optical and infrared morphology classes tend to be different for the same object. Assessment of flux variation behavior with respect to (circum)stellar properties reveals correlations of variability parameters with H alpha emission and with effective temperature. Overall, our results point to multiple origins of young star variability, including circumstellar obscuration events, hot spots on the star and/or disk, accretion bursts, and rapid structural changes in the inner disk.